IMPLEMENTASI PENGENDALIAN MUTU PADA PENDIDIKAN INFORMAL DI INDONESIA - Innayatul Magfirah; Romi Faslah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Informal education is a learning pathway that takes place within the family and community environment through natural, flexible, and continuous learning processes. This study aims to examine the implementation of quality control in informal education in Indonesia, particularly from the Islamic perspective which emphasizes the development of character, morality, and spirituality from an early age. This research employs a qualitative approach using library research methods, supported by descriptive-analytical and content analysis techniques. The findings indicate that the family functions as the primary and foundational educational institution in shaping a child's personality. The effectiveness of informal education can be observed through the development of moral, spiritual, social, and cognitive aspects reflected in a child's behavior and interaction patterns. The implementation of quality control in informal education can be strengthened through religious habituation, parental role modeling, supportive social environments, and collaborative efforts among families, communities, and religious institutions. Therefore, informal education holds strategic significance in cultivating noble character and strong personality foundations as an integral part of the national education system.